Surgical Treatment for Thrombus Straddling a Patent Foramen Ovale - Oliveira,Marcos Aurélio Barboza de (2016)
Abstract We present a case of a 41-year-old female with deep vein thrombosis after abdominal surgery. The patient quickly developed severe pulmonary embolism and stroke representative of paradoxical embolism. Echocardiography showed a thrombus straddling a patent foramen ovale, which was confirmed intraoperatively. An accurate diagnosis and rapid treatment decisions are crucial for preventing patient deterioration in the form of new pulmonary embolisms or stroke.